A computed tomography–based method for the assessment of canine retrobulbar cone volume for ophthalmic anaesthesia. (September 2021) - Greco, Adelaide; Costanza, Dario; Senatore, Andrea; Bruzzese, Dario; Micieli, Fabiana; Chiavaccini, Ludovica; Di Giancamillo, Mauro; Della Valle, Giovanni; Vesce, Giancarlo; Brunetti, Arturo; Meomartino, Leonardo
Abstract: Objective: To develop a comprehensive formula for calculating the volume of local anaesthetic solution used for retrobulbar anaesthesia in dogs with different skull morphologies. Study design: Retrospective cohort imaging study. Animals: Skull computed tomography (CT) images of 188 dogs of different breeds collected between January 2009 and December 2017. Methods: Anatomical integrity of the orbit and adjacent structures, presenting complaint, clinical signs and CT findings were verified to exclude ocular abnormalities. The volume of the retrobulbar cone of 376 eyes was calculated using CT scans of the dogs' skulls. Additional data recorded included morphology of the skull, body weight, sex and size of the dogs, all of which were matched for possible association to the retrobulbar cone volume through univariable and multivariable linear regression models. Results of linear regression models were expressed as estimated beta coefficients with the corresponding 95% confidence intervals (95% CIs). Results: Using univariate analysis, the retrobulbar cone volume was positively associated with weight and male sex. In addition, brachycephalic and dolichocephalic dogs showed a larger retrobulbar cone volume than mesocephalic dogs, while sex was no longer significantly associated with the retrobulbar cone volume. In multivariate analysis, when considering all variables in the model, weight emerged as the strongest predictor (beta coefficient: 0.062 mL kg –1, 95% CI: 0.056–0.067 mL kg –1, p < 0.001). Conclusions: and clinical relevance In the veterinary literature, there is no agreement on the precise volume of local anaesthetic solution that should be used to achieve intraconal retrobulbar anaesthesia in dogs. Here we suggest a formula to calculate the retrobulbar cone volume and, accordingly, the injection volume of local anaesthetic solution for effective retrobulbar anaesthesia.